MORPHOLOGICAL CHARACTERIZATION OF ORCHARDGRASS (Dactylis glomerata L.) NATURALLY SPREAD IN EASTERN ANATOLIA, TÜRKIYE - Ö. Arvas; A. Nabhan (Journal of Animal and Plant Sciences, 2024)
Orchardgrass (Dactylis glomerata L.) is a cold-resistant, perennial and one of the main forage species of meadows and pastures. A total of 9 morphological traits were considered for the morphological characterization of the orchardgrass, which is naturally distribusted in the flora of 43 different locations in 8 provinces of the Eastern Anatolia of Türkiye. According to the analysis of variance; significant differences were determined between genotypes in terms of the morphological traits examined. These differences resulted in a high degree of phenotypic variation. In addition, correlation coefficient analysis showed a significant (P<0.01) and positive relation between most of the traits examined. The highest correlation coefficient was between plant height and peduncle length (0.864**), flag leaf length and flag leaf width (0.765**), flag leaf length and panicle length (0.734**) The first five Principal components (PCA) explained 70.31 % of the total variation in orchardgrass genotypes. The highest plant height and maximum number of tillers, which are important for grass yield and reproduction, were determined in M75 (77.57 cm) and R163 (27.85 per/plant) respectively. The high morphological variation among orchardgrass genotypes indicates the existence of a rich genetic population and can be considered as breeding material.
Keywords: Türkiye; Eastern Anatolia; morphological characterization; phenotypic variation; Dactylis glomerata; orchardgrass